2022
DOI: 10.1615/plasmamed.2023047705
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Possible Cytogenetic and Immunological Effects of Cold Atmospheric Pressure Plasma Jet on Whole Blood Cultures of Vitiligo Patients

Abstract: Vitiligo is a multifactorial disorder disease characterized by loss of functional melanocytes, genetic damage, excess inflammation, autoimmune dysfunction, and extreme oxidative stress in lesions. Unfortunately, there is not enough response to obtainable therapies nowadays. The present study was designed using a plasma jet powered by a Tesla coil, which can be used for generating cold atmospheric pressure plasma jet (CAPPJ) from dielectric barrier discharge. The subject samples were categorized into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This innovative therapeutic approach harnesses the power of low-temperature plasma to stimulate repigmentation in areas affected by Vitiligo, a chronic skin disorder characterized by depigmented patches. Research studies and clinical trials have shown promising results, highlighting the potential of CAP in enhancing melanocyte activity and promoting the restoration of normal pigmentation [143]. Zhai et al [144] conducted a study on the efficacy and safety of PAH (Cold Atmospheric Plasma) in vitiligo, utilizing mouse models and patients with active focal vitiligo.…”
Section: Vitiligomentioning
confidence: 99%
“…This innovative therapeutic approach harnesses the power of low-temperature plasma to stimulate repigmentation in areas affected by Vitiligo, a chronic skin disorder characterized by depigmented patches. Research studies and clinical trials have shown promising results, highlighting the potential of CAP in enhancing melanocyte activity and promoting the restoration of normal pigmentation [143]. Zhai et al [144] conducted a study on the efficacy and safety of PAH (Cold Atmospheric Plasma) in vitiligo, utilizing mouse models and patients with active focal vitiligo.…”
Section: Vitiligomentioning
confidence: 99%